Trust In Knowledge Transfer Process Via E-Banking Web Site Among Undergraduate Perspective - Ali Hussein Ali Abu Zaid
Electronic banking web site is a timnn of sell-; erv ice technology. The numbers of Internet users have increased dramatically, but most of them are reluctant to provide sensitive personal information to banking web sites and they faced the negative incidents Of their bank accounts and their transactions blithe tampered because they do not trust c-banking web site. This research has adapted Szulanski'5 Widely accepted and recognized knowledge transfer model as a Ions to study trust factor. The model consists Of I Out. stages: initiation: implementation: ramp-up: and integration. This research evaluate the trust factor Which are affecting the knowledge transfer process via c-banking web site among c-banking clients. and also determine in which stage of knowledge transfer process of concern regarding trust issues in Malaysian context. Primary data collected from 372 respondents. through a structured questionnaire. Statistical analysis, descriptive statistics used to explain demographic profile of respondents and also correlation analyses were used to know trend of interact bank web site use affecting knows ledge transfer process in e-banking web site. Result has shown that the trust factor had a positive effect in all knovwwled, -, e transfer process stage;, and trust factor has a high correlation with initiation stage via electronic banking web site in Malaysia. This research contributes to the understanding of how local context can shape perceptions of the criticality of trust affecting KT in c-banking weh site, Provided IT practitioners involved Al developing web site, particularly c-bank Web site, provided with insight; that can contribute to making a web site a successful channel for the dcliyery of bank knowledge resources to users